Subspecialist training program in pediatric otorhinolaryngology of UEMS ORL-HNS section. (January 2017) - Baudoin, Tomislav
Abstract: The ORL Section and Board of Otorhinolaryngology-Head and Neck Surgery of the European Union of Medical Specialists (UEMS) developed pediatric ORL subspecialty program. The program was created with support and consultation of the European Society of Pediatric Otorhinolaryngology. It is divided into four sections: Pediatric Otology, Pediatric Rhinology and Facial Plastic Surgery, Pediatric Laryngology and Phoniatrics and Pediatric Head and Neck Surgery. After completion of the program, the trainee is supposed to achieve an advanced level of competency. The aim of the program is to serve as a guideline for training centers, enabling them to meet the European Standard as set out by the European Board of UEMS through competency based assessments.